A Diagnostic Model for Dementia in Clinical Practice—Case Methodology Assisting Dementia Diagnosis - Elisabet Londos (Diagnostics, 2015)
Dementia diagnosis is important for many different reasons. Firstly, to separate dementia, or major neurocognitive disorder, from MCI (mild cognitive impairment), mild neurocognitive disorder. Secondly, to define the specific underlying brain disorder to aid treatment, prognosis and decisions regarding care needs and assistance. The diagnostic method of dementias is a puzzle of different data pieces to be fitted together in the best possible way to reach a clinical diagnosis. Using a modified case methodology concept, risk factors affecting cognitive reserve and symptoms constituting the basis of the brain damage hypothesis, can be visualized, balanced and reflected against test results as well as structural and biochemical markers. The model’s origin is the case method initially described in Harvard business school, here modified to serve dementia diagnostics.